Targeting envelope proteins of poxviruses to repurpose phytochemicals against monkeypox: An in silico investigation - Gulati, Pallavi; Chadha, Jatin; Harjai, Kusum; Singh, Sandeepa (Frontiers in Microbiology, 2023)
The monkeypox virus (MPXV) has become a major threat due to the increasing global caseload and the ongoing multi-country outbreak in non-endemic territories. Due to limited research in this avenue and the lack of intervention strategies, the present study was aimed to virtually screen bioactive phytochemicals against envelope proteins of MPXV via rigorous computational approaches. Molecular docking, molecular dynamic (MD) simulations, and MM/PBSA analysis were used to investigate the binding affinity of 12 phytochemicals against three envelope proteins of MPXV, viz., D13, A26, and H3. Silibinin, oleanolic acid, and ursolic acid were computationally identified as potential phytochemicals that showed strong binding affinity towards all the tested structural proteins of MPXV through molecular docking. The stability of the docked complexes was also confirmed by MD simulations and MM/PBSA calculations. Results from the iMODS server also complemented the findings from molecular docking and MD simulations. ADME analysis also computationally confirmed the drug-like properties of the phytochemicals, thereby asserting their suitability for consumption. Hence, this study envisions the candidature of bioactive phytochemicals as promising inhibitors against the envelope proteins of the MPXV, serving as template molecules that could further be experimentally evaluated for their efficacy against monkeypox.